Self-Selection Patterns in Mexico-U.S. Migration: The Role of Migration Networks - McKenzie, David (2012)
This paper examines the role of migration networks in determining self-selection patterns of Mexico-U.S. migration. A simple theoretical framework shows the impact of networks on migration incentives at different education levels and how this affects the composition of migrant skills. Empirically, we find positive or education-neutral selection in communities with weak migrant networks but negative self-selection in communities with stronger networks. This is consistent with high migration costs driving positive or intermediate self-selection, as advocated by Chiquiar and Hanson (2005), and with negative self-selection being driven by lower returns to education in the United States than in Mexico, as advocated by Borjas (1987).